2016
DOI: 10.1371/journal.pone.0147380
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Histone Deacetylase 2 (HDAC2) in Peripheral Blood Monocytes (PBMCs) of COPD Patients

Abstract: BackgroundHistone deacetylase 2 (HDAC2) is a class I histone deacetylase family member that plays a critical role in suppressing inflammatory gene expression in the airways, lung parenchyma, and alveolar macrophages in patients with chronic obstructive pulmonary disease (COPD). However, the expression of HDAC2 in peripheral blood monocytes (PBMCs), nuclear factor kappa B (NF-κB) p65, and serum inflammatory cytokine levels in COPD patients, smokers, and non-smokers remains unclear.MethodsPBMCs were obtained fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 34 publications
0
30
0
1
Order By: Relevance
“…In this sense, the phenotype of peripheral blood mononuclear cell (PBMC) is controlled through epigenetic signals that are involved in both activation and repression of specific genes involved in the immune response as well as in the production of inflammatory mediators (Shanmugam and Sethi, 2013). Regarding COPD, previous work demonstrated altered levels of histone deacetylase (HDAC) in immune cells from patients compared to matched controls (Tan et al, 2016;To et al, 2012). Interestingly, the histone hyperacetylation status in PBMC of COPD patients was also accompanied by higher expression of NF-κB and increased systemic levels of TNF-α and IL-8 (Ito et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, the phenotype of peripheral blood mononuclear cell (PBMC) is controlled through epigenetic signals that are involved in both activation and repression of specific genes involved in the immune response as well as in the production of inflammatory mediators (Shanmugam and Sethi, 2013). Regarding COPD, previous work demonstrated altered levels of histone deacetylase (HDAC) in immune cells from patients compared to matched controls (Tan et al, 2016;To et al, 2012). Interestingly, the histone hyperacetylation status in PBMC of COPD patients was also accompanied by higher expression of NF-κB and increased systemic levels of TNF-α and IL-8 (Ito et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence revealed NF-κB is involved in the deacetylase HDAC2-mediated histone H3 lysine 27 acetylation (H3K27ac). 33,34 Therefore, we suspected HOXA-AS2 may regulate the SP7 expression in a NF-κB-mediate HDAC2 acetylation manner.…”
Section: Hoxa-as2 Epigenetically Regulates Sp7 Expression By a Nf-κmentioning
confidence: 99%
“…The nuclear factor kappa-lightchain-enhancer of activated B cells (NF-κB) transcription factor plays an important role in this. Upregulated NF-κB activity has been reported in asthma [57] and COPD [51,58]. NF-κB is subject to regulation by lysine acetylations [59].…”
Section: Macrophages: Selective Regulation Of the Nf-κb Transcriptionmentioning
confidence: 99%
“…In more recent studies, decreased HDAC2 expression was also found in PBMCs and lymphocytes in COPD [50,51]. In COPD, the decreased HDAC2 expression and activity can be linked to glucocorticoid resistance [52].…”
mentioning
confidence: 93%